SIFAT FISIKO KIMIA DAMAR MATA KUCING HASIL PEMURNIAN TANPA PELARUT - R. Esa Pangersa Gusti; Zulnely (BRIN Publishing, 2014)
Mata kucing dammar has long become remarkable export commodity, most of which unfortunately is still in naturalform (chunk-shapped exudates) obtained from the tapping of its host trees (Shorea javanica). Accordingly, such dammarstill contains large amount of impurities thereby lowering its qualities or trade values. Consequently, this necessitates athorough purification attempt to enhance the dammar's added-value. The dammar purification prevalently uses organicsolvent. However, the market demand for the solvent-free dammar products currently tends to increase commensurate withthe advancement in dammar usage for drugs/ medicine and food industries. In relevant, purification of mata-kucingdammar was experimented using manual heating system, rather than organic solvent. Result revealed physico-chemicalproperties of the heat-purified dammar were not significantly different from those of natural dammar (without purificationtreatment) as well as of the solvent-purified dammar. Even, with respect to ash content (impurities) and toluene insolubility,the heat-purified dammar seemed to be better than the natural dammar. GC-MS analysis revealed there were five majorchemical compounds with relatively large contents in heat-purified dammar. Such phenomena were similar to those in thenatural dammar, with the contents of those compounds in the heat-purified dammar slightly higher.